2019
DOI: 10.1111/epi.15541
|View full text |Cite
|
Sign up to set email alerts
|

Interictal coupling of HFOs and slow oscillations predicts the seizure‐onset pattern in mesiotemporal lobe epilepsy

Abstract: Objective Low‐voltage fast activity (LVF) and low‐frequency high‐amplitude periodic spiking (PS) are the two most common seizure‐onset patterns in mesiotemporal lobe epilepsy, with different underlying mechanisms, pathology, and postsurgical outcome. The present work aims to investigate whether specific coupling patterns of high‐frequency oscillations (HFOs >80 Hz) and low‐frequency waves in the interictal period may distinguish these two patterns, and also seizure‐onset zone (SOZ) from non‐SOZ as a secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…In line with a previous study 14 , our study demonstrated that θ band was the main low frequency band modulating ictal-ripple activities and α-and β-ripple PAC showed the same tendency as the θ-ripple PAC with a weaker PAC though. Moreover, it is reported that coupling with θ waves and HFOs well discriminated normal brain regions from SOZ 28 . Therefore, we inferred that ripple activities occurring during early seizure evolution were modulated by θ rhythm.…”
Section: Discussionmentioning
confidence: 96%
“…In line with a previous study 14 , our study demonstrated that θ band was the main low frequency band modulating ictal-ripple activities and α-and β-ripple PAC showed the same tendency as the θ-ripple PAC with a weaker PAC though. Moreover, it is reported that coupling with θ waves and HFOs well discriminated normal brain regions from SOZ 28 . Therefore, we inferred that ripple activities occurring during early seizure evolution were modulated by θ rhythm.…”
Section: Discussionmentioning
confidence: 96%
“…In line with a previous study 14 , our study demonstrated that θ band was the main low frequency band modulating ictal-ripple activities and α-and β-ripple PAC showed the same tendency as the θ-ripple PAC with a weaker PAC though. Moreover, it is reported that coupling with θ waves and HFOs well discriminated normal brain regions from SOZ 28 . Therefore, we inferred that ripple activities occurring during early seizure evolution were modulated by θ rhythm.…”
Section: Discussionmentioning
confidence: 96%
“…In humans, the dynamics of the SWO have demonstrated to be highly reproducible within and across subjects, providing information about the general state of the cerebral cortex and suggesting its applicability as a method to unravel functional circuits (Massimini et al, 2004). The analysis of the SWO has been used to detect neurophysiological alterations in humans and in a mouse models of neurological disorders such as; Alzheimer's disease (Busche et al, 2015),Down syndrome (Ruiz-Mejias et al, 2016), or Epilepsy (Amiri et al, 2019), among others. Here, we analysed the electrophysiological properties of MSNs, their evoked visual responses and the slow and the fast components of their oscillatory activity, and we found that the Up states of the SWO are useful method to identify brain circuits.…”
Section: Discussionmentioning
confidence: 99%